Lord Of The Flies - A Novel In The Robinsonade Genre (Eurasian Journal of Humanities and Social Sciences, 2024)
This article analyzes the novel “Lord of the Flies” by the English writer William Golding. This work is assessed as a work written in the Robinsonade genre.